Results from a first-in-human phase I safety trial to evaluate the use of a vascularized pericranial/temporoparietal fascial flap to line the resection cavity following resection of newly diagnosed glioblastoma - Doron, Omer; Wong, Tamika; Ablyazova, Faina; Singha, Souvik; Cavallaro, Julianna; Ben-Shalom, Netanel; D’Amico, Randy S.; Harshan, Manju; McKeown, Amy; Zlochower, Avraham; Langer, David J.; Boockvar, John A. (Journal of neuro-oncology, 2024)
Purpose The efficacy of systemic therapies for glioblastoma (GBM) remains limited due to the constraints of systemic toxicity and blood–brain barrier (BBB) permeability. Temporoparietal fascial flaps (TPFFs) and vascularized peri cranial flaps (PCF) are not restricted by the blood–brain barrier (BBB), as they derive their vascular supply from branches of the external carotid artery. Transposition of a vascularized TPFF or PCF along a GBM resection cavity may bring autologous tissue not restricted by the BBB in close vicinity to the tumor bed microenvironment, permit ingrowth of vascular channels fed by the external circulation, and offer a mechanism of bypassing the BBB. In addition, circulating immune cells in the vascularized flap may have better access to tumor-associated antigens (TAA) within the tumor microenvironment. We conducted a first-in-human Phase I trial assessing the safety of lining the resection cavity with autologous TPFF/PCF of newly diagnosed patients with GBM. Methods 12 patients underwent safe, maximal surgical resection of newly diagnosed GBMs, followed by lining of the resection cavity with a pedicled, autologous TPFF or PCF. Safety was assessed by monitoring adverse events. Secondary analysis of efficacy was examined as the proportion of patients experiencing progression-free disease (PFS) as indicated by response assessment in neuro-oncology (RANO) criteria and overall survival (OS). The study was powered to determine whether a Phase II study was warranted based on these early results. For this analysis, subjects who were alive and had not progressed as of the date of the last follow-up were considered censored and all living patients who were alive as of the date of last follow-up were considered censored for overall survival. For simplicity, we assumed that a 70% PFS rate at 6 months would be considered an encouraging response and would make an argument for further investigation of the procedure. Results Median age of included patients was 57 years (range 46–69 years). All patients were Isocitrate dehydrogenase (IDH) wildtype. Average tumor volume was 56.6 cm 3 (range 14–145 cm 3 ). Resection was qualified as gross total resection (GTR) of all of the enhancing diseases in all patients. Grade III or above adverse events were encountered in 3 patients. No Grade IV or V serious adverse events occurred in the immediate post-operative period including seizure, infection, stroke, or tumor growing along the flap. Disease progression at the site of the original tumor was identified in only 4 (33%) patients (median 23 months, range 8–25 months), 3 of whom underwent re-operation. Histopathological analyses of those implanted flaps and tumor bed biopsy at repeat surgery demonstrated robust immune infiltrates within the transplanted flap. Importantly, no patient demonstrated evidence of tumor infiltration into the implanted flap. At the time of this manuscript preparation, only 4/12 (33%) of patients have died. Based on the statistical considerations above and including all 12 patients 10/12 (83.3%) had 6-month PFS. The median PFS was 9.10 months, and the OS was 17.6 months. 4/12 (33%) of patients have been alive for more than two years and our longest surviving patient currently is alive at 60 months. Conclusions This pilot study suggests that insertion of pedicled autologous TPFF/PCF along a GBM resection cavity is safe and feasible. Based on the encouraging response rate in 6-month PFS and OS, larger phase II studies are warranted to assess and reproduce safety, feasibility, and efficacy. Trial registration number and date of registration for prospectively registered trials ClinicalTrials.gov ID NCT03630289, dated: 08/02/2018.